An autopsy case of ruptured liver metastases from small cell lung cancer: A case report and literature review. (2020) - Goto, Yuki; Tobino, Kazunori; Yoshimine, Kohei; Sueyasu, Takuto; Okahisa, Masanobu; Sakabe, Mitsukuni; Tsuruno, Kosuke
Abstract: A 50-year-old male presented to our hospital complaining of dry cough and slight fever. A chest CT scan showed a mass in the right upper lung lobe, pleural effusion on both sides, and multiple liver tumors. He was diagnosed with small cell lung cancer (SCLC), and then antitumor chemotherapy was started. Thereafter, his condition deteriorated rapidly, and died 2 days later. An autopsy revealed that the cause of death was ruptured liver metastases. SCLC is a highly invasive disease and often metastasizes to the liver, but the rupture of liver metastases is rare. Clinical features and imaging findings were of a great help in diagnosing ruptured hepatic metastasis. Physicians need to pay attention to this condition, especially after chemotherapy has initiated.